Impact of Sophrology on cardiopulmonary fitness in teenagers and young adults with a congenital heart disease: The SOPHROCARE study rationale, design and methods. (April 2020) - Moreau, Johan; Lavastre, Kathleen; Romieu, Huguette; Charbonnier, Françoise; Guillaumont, Sophie; Bredy, Charlene; Abassi, Hamouda; Werner, Oscar; De La Villeon, Gregoire; Requirand, Anne; Auer, Annie; Matecki, Stefan; et al.
Highlights: Exercise capacity in patients with CHD is lower than in the general population. Non-invasive relaxation therapy may be effective in patients with dyspnoea. Evidence based-medicine on relaxation therapy in the CHD population is poor. This trial will assess the impact of Sophrology on exercise capacity in CHD patients. Abstract: Background: Recent advances in the field of congenital heart disease (CHD) have significantly improved the overall prognosis. Now more attention is being given to health-related quality of life (HRQoL) and promotion of physical activity. Non-invasive relaxation therapy may be effective in cardiac patients concerned with exercise-induced dyspnoea. The SOPHROCARE randomised trial aims to assess the impact of Caycedian Sophrology on cardiopulmonary fitness in adolescents and young adults with CHD. Methods: The SOPHROCARE trial is a nationwide, multicentre, randomised, controlled study in CHD patients aged from 13 to 25 years old. Patients will be randomised into 2 groups (8 Sophrology group sessions vs. no intervention). The primary outcome is the change in percent predicted maximum oxygen uptake (VO2max ) between baseline and 12-month follow-up. A total of 94 patients in each group is required to observe a significant increase of 10% in VO2max with a power of 80% and an alpha risk of 5%. The secondary outcomes are: clinical outcomes, cardiopulmonary exercise test parameters (VE/VCO2 slope, ventilatory anaerobic threshold, oxygen pulse, respiratory response to hypercapnia), health-related quality of life score (PedsQL), physical and psychological status. Conclusion: After focusing on the survival in CHD, current research is opening on secondary prevention and patient-related outcomes. We sought to assess in the SOPHROCARE trial, if a Sophrology program, could improve exercise capacity and quality of life in youth with CHD. Trial registration: Clinicaltrials.gov (NCT03999320).